Analysis of qualitycontrolinvanameshrimpfreezingprocess (litopenaeus vannamei) with six sigma - Binti Sri Rahayu; Iffan Maflahah; Asfan Asfan (Universitas Darussalam Gontor, 2020)
PT. XYZ is a company that processes vaname shrimp into frozen shrimp products. Frozen shrimp is a product that serves for export, so that it must meet predetermined quality standards. Quality measurement is determined to monitor a process under controlled or uncontrolled conditions. The method of measuring is the six sigma method. The purpose of this research is an alarm that is responsive, alert, and alert, attentive, alert and responds to frozen products using the six sigma method at PT. XYZ. The frozen peeled shrimp production process stages start from receiving raw materials, cutting shrimp heads, quality sorting and size separation, peeling the skin and taking the intestines, soaking, freezing shrimp, packaging, metal detection, and product packaging. The results showed that 1,904 frozen peeled shrimp with 43 defective products had a sigma level of 3,22 with possible damage of 40.363,38 for one million products (DPMO) and the proportion of wrong causes of defects, namely 44,2%. The proposed improvementsto be carried out are to provide direction and advice to employees to be careful and thorough, and the company offers a unique tool for cleavage of shrimp